Numerical simulation of an oscillating water column device using a code based on NaviereStokes equations - Teixeira, P. (2013)
The study of ways of converting ocean wave energy into a useful one and the improvement of the existing equipment are complex engineering problems and very important issues in today’s society. In this paper, the onshore oscillating water column device, in a 10 m deep channel subjected to 1 m high incident wave and wave periods from 4 s to 15 s, is investigated. The numerical analyses are carried out using Fluinco model that deals with incompressible flow problems based on the NaviereStokes equations and employs the two-step semi-implicit TayloreGalerkin method. An aerodynamic model is implemented in the algorithm to determine the air pressure that is imposed on the free surface. Analyses are divided into two sections. In the first section, the flow variables obtained by Fluinco and the commercial model Fluent are compared and similar results are obtained. In the second section, an investigation of the chamber geometry and turbine characteristic relation that provide the best device performance is carried out. In this case, variations in the front wall depth, the chamber length, the turbine characteristic relation and the chamber height, are made.